1993
DOI: 10.1111/j.1741-2358.1993.tb00085.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of root surface caries amongst Irish adults

Abstract: In a national survey of adult dental health conducted in the Republic of Ireland in 1989/90 a total of 1,527 subjects aged 25 and older were examined for root surface caries. It was found that the prevalence of root surface caries was highest in older age groups and also amongst males, residents of non-fluoridated communities and those earning low incomes. Tooth loss masked the potential prevalence of root surface caries. With more persons retaining their natural teeth into middle and old age the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A previous study published in 1993 reported on the prevalence of root caries in Irish adults [7]; 94 of the participants were dentate and aged over 65. This study reported the mean RCI of dentate over 65 year olds as 11.7 for those living in fluoridated areas and 18.9 for those living in a non-fluoridated area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study published in 1993 reported on the prevalence of root caries in Irish adults [7]; 94 of the participants were dentate and aged over 65. This study reported the mean RCI of dentate over 65 year olds as 11.7 for those living in fluoridated areas and 18.9 for those living in a non-fluoridated area.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in exposed root surfaces in the over 65 age group predisposes this group to a higher prevalence of root caries than younger populations [5]. Estimating the prevalence of root caries can be challenging as loss of teeth confounds the data and diagnostic criteria and methods of reporting the data differ between studies [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the mid-1980s a series of studies on root canes started being published and the RCI evidently was in use. Having now just completed a comprehensive review of the root caries literature for a textbook chapter, I would state that the RCI appears to have proved useful to the epidemiologic research community and is currently one of the two major methods of reporting root caries, the other method being a raw DFS count of root canes lesions per person (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Both are often reported in the same study (6-111, giving what is probably the best overall, and most interpretable, view of the disease of root caries.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for further research in this area as there are insufficient good quality randomised clinical trials currently available to guide practitioners. In particular, there is a need to evaluate restorative materials in a more generalised population, as many of the studies included in this systematic review were confined to post‐radiation, xerostomic patients, which may be atypical of the older adult dental patient. Increased adherence to CONSORT guidelines for reporting the results of any future RCTs is must also be encouraged to facilitate future systematic review and meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%